How to Manage Numerical Abilities in Algebra Material? - Munifah, Munifah; Romadhona, Annisa Nurhuda; Ridhona, Ilma; Ramadhani, Rahmi; Umam, Rofiqul; Tortop, Hasan Said (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
Numerical ability is very help students understand the material, analyze any problems, and apply math concepts in daily life so that numerical abilities of students is a factor that can affect learning outcomes. Determine the effect of learning model Scramble and learning model with SAVI (Somatic, Auditory, Visual, and Intellegence) on the ability of numerical be the purpose of this article. The design of the research used Quasy Experimental Design, with the instrument used for the study in the form of test numerical ability. Data analysis used the T-test. Based on the results of the research concluded that the learning model Scrambler and learning model SAVI has a significant influence on numerical ability. And both of them is a model of learning which is equally effective against numerical abilities in order to improve learning outcomes is more optimal. But model pembelajaran SAVI is more effective than learning models scramble